(untitled) (Global Journal of Management and Business Research, 2018)
The purpose of this paper, relating to occupational safety and health committees (OSHCs), is to discover the mediating effects of both competency of OSHCs and scope of OSHCs, respectively, on the relationship between management’s commitment - in terms of both active management commitment and passive management commitment, respectively - and effective OSHCs in Malaysia. Using survey data from 231 manufacturing firms, operating in Malaysia, the study empirically examined the influence of active management commitment, passive management commitment, competency of OSHCs and scope of OSHCs on the perceived effectiveness of OSHCs. Respondents of the survey method, who were members of OSHCs, perceived all five variables at the medium level, with scope of OSHCs having the highest mean value (mean = 3.70) and active management commitment the lowest mean value (mean = 3.11). Multiple regression analyses suggested that all variables, excluding passive management commitment, had significant positive associations with perceived effectiveness of OSHCs, with competency of OSHCs, having the strongest positive association with it. Findings also suggested that both competency of OSHCs and scope of OSHCs, partially mediated the relationships, between both types of management commitment and perceived effectiveness of OSHCs. This paper underlines the importance of management’s commitment, especially active management commitment, to occupational safety and health (OSH) in general and to OSHCs in particular, as this would be manifested in enhancing the competency of OSHCs, and enabling the broader functioning of OSHCs, leading inevitably to OSHCs perceived as more effective.